Huangkui lianchang decoction attenuates experimental colitis by inhibiting the NF-κB pathway and autophagy - Cheng, Xudong; Du, Jun; Zhou, Qing; Wu, Bensheng; Wang, Haodong; Xu, Zhizhong; Zhen, Shuguang; Jiang, Jieyu; Wang, Xiaopeng; He, Zongqi (Frontiers in Pharmacology, 2022)
Ulcerative colitis (UC) is a chronic inflammatory colorectal disease characterized by excessive mucosal immune response activation and dysfunction of autophagy in intestinal epithelial cells. Traditional herbal preparations, including the Huangkui lianchang decoction (HLD), are effective in UC clinical treatment in East Asia, but the underlying mechanism is unclear. This study evaluated the therapeutic effects and associated molecular mechanisms of HLD in UC in vivo and in vitro. A C57BL/6 UC mouse model was established using 2.5% dextran sulfate sodium. The effects of HLD on the colonic structure and inflammation in mice were evaluated using mesalazine as the control. The anti-inflammatory effects of HLD were assessed using disease activity index (DAI) scores, histological scores, enzyme-linked immunosorbent assay, immunohistochemistry, immunofluorescence, and western blotting. HLD displayed a protective effect in UC mice by reducing the DAI and colonic histological scores, as well as levels of inflammatory cytokines and NF-κB p65 in colonic tissues. NCM460 lipopolysaccharide-induced cells were administered drug serum-containing HLD (HLD-DS) to evaluate the protective effect against UC and the effect on autophagy. HLD-DS exhibited anti-inflammatory effects in NCM460 cells by reducing the levels of inflammatory cytokines and increasing interleukin 10 levels. HLD-DS reduced p-NF-κB p65, LC3II/I, and Beclin 1 expression, which suggested that HLD alleviated colitis by inhibiting the NF-κB pathway and autophagy. However, there was no crosstalk between the NF-κB pathway and autophagy. These findings confirmed that HLD was an effective herbal preparation for the treatment of UC.